On Signomial Constrained Optimal Control Problems - Savin Treanta (Communications in Advanced Mathematical Sciences, 2019)
In this paper, using the notions of variational differential system, adjoint differential system and modified Legendrian duality, we formulate and prove necessary optimality conditions in signomial constrained optimal control problems.